2007
DOI: 10.1016/j.canlet.2006.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Importance of xeroderma pigmentosum group D polymorphisms in susceptibility to ovarian cancer

Abstract: The purpose of this study was to evaluate the role of XPD genotypes as genetic indicator of susceptibility to ovarian cancer. We have used a case-control study. We analysed DNA samples from 141 ovarian cancer patients and 202 control subjects, for three XPD polymorphisms using PCR-RFLP. We observed that Asn312Asn XPD genotype carriers have increased susceptibility of ovarian cancer (OR=2.46 95% CI 1.20-5.06; P=0.015). Furthermore, we found that carriers of Gln751Gln XPD genotype have an increased susceptibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
(57 reference statements)
0
4
1
Order By: Relevance
“…Our results are inconsistent with a previous report that demonstrated an association between XPD codon 312 and an increased susceptibility to ovarian cancer during early stages of the disease (Costa et al, 2007). In addition, an interaction between the XPD codon 312 Asp/ Asn and Asn/Asn genotypes and X-ray-and UV-light-induced chromosome aberrations in healthy individuals has also been reported (Au et al, 2003).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are inconsistent with a previous report that demonstrated an association between XPD codon 312 and an increased susceptibility to ovarian cancer during early stages of the disease (Costa et al, 2007). In addition, an interaction between the XPD codon 312 Asp/ Asn and Asn/Asn genotypes and X-ray-and UV-light-induced chromosome aberrations in healthy individuals has also been reported (Au et al, 2003).…”
Section: Discussioncontrasting
confidence: 99%
“…Hsieh et al (2008) and Camargo-Kosugi et al (2009) showed associations between endometriosis and XRCC4 (codon 247, promoter 1394) polymorphisms and between endometriosis and the P27 (codon 109) polymorphism, respectively. Costa et al (2007) also demonstrated an association of XPD codon 312 and 751 polymorphisms with an increased susceptibility to ovarian cancer.…”
Section: Introductionmentioning
confidence: 85%
“…Common genetic alterations (e.g. polymorphisms), with possible effects on function and/or protein expression, within genes involved in essential cellular pathways, such as carcinogen metabolism, DNA repair, cell cycle control and cell proliferation, could predispose individuals to cancer [ 15 , 23 - 25 ], including breast cancer [ 15 , 26 - 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al (2002) did not show an association between these two SNP in ERCC2 and breast cancer risk whereas a lower A allele frequency in ERCC2 Asp312Asn was found in a Chinese population by Zhang et al (2005) [ 5 , 36 ]. On the contrary, a case-control study in Portugal revealed that women with the Asn312Asn or the Gln751Gln genotype presented a three-fold risk of ovarian cancer in comparison with heterozygous or wild-type homozygous women [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The DNA helicase encoded by the excision repair cross-complementing group 2 gene ERCC2 (formely XPD ) is one of seven nucleotide excision repair enzymes that cause Xeroderma Pigmentosum when mutated in germ line [ 2 ]. Several polymorphisms have been identified in this gene and particularly the Asp312Asn ERCC2 polymorphism which consists of the substitution of a G to A resulting in an amino acid change in the coding region, and the Lys751Gln which consists in a A to C substitution in the coding region [ 3 ]. A change of amino acid is able to modify the effect of protein more or less, which can translate by an effect on the systems of repair and consequently on the carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%